Research Note: Optimizing wheat productivity through improved techniques for in situ moisture conservation in a micro watershed under sub-tropical region of North-Western India - Arora, Sanjay; Hadda, M.S. (Annals of Tropical Research, 2008)
The sub-montane rainfed region of North-West India has sloping topography, poor soil structure, deep water table and suffers from uneven distribution of rainfall in space and time. In a on-farm experiment on wheat conducted in the foothill region of Punjab, soil moisture storage increased to 7.7, 12.8 and 15.4 % in treatment T2 (minor land shaping + NPK), T3 (T2 + 25 % replacement through FYM) and T4 (T3 + ridge sowing + Zn + herbicides), respectively, over T1 (farmers’ practice as control). Maximum increase in plant height of 28.7 per cent was observed in T4 followed by 19.9 % in T3 and 13.6 % in T2 treatment compared to T1. Number of grains per ear increased by 14.6, 25.1 and 33.7 % through T2, T3 and T4 treatments, respectively over that in treatment T1. The grain and straw yield of wheat significantly increased by 38.6 and 65.3 % in T2, 56.3 and 76.6 % in T3 and 63.3 and 88.2 % in T4 treatment respectively over T1 treatment (control). Maximum monetary returns were obtained in T4 treatment.